Analysis of Behavioral Facilitation Information During Disasters Based on Reader Attributes and Personality Traits - Nadamoto, Akiyo; Wakasugi, Kosuke; Suzuki, Yu; Kumamoto, Tadahiko (Informatica, 2025)
During disasters, a large volume of messages are posted on social networking services (SNS). Some of these messages include ``behavioral facilitation information,'' which either encourages or discourages specific actions. However, the interpretation of such information is contingent upon the personality traits of the individuals affected. In this study, we hypothesize that victims' personality traits influence their perception of behavioral facilitation information, and we analyze the characteristics of these differences. Focusing on typhoons, we propose a method for extracting behavioral facilitation information from posts on X (formerly Twitter) during typhoon-related disasters. The extracted behavioral facilitation information is then classified into four content-based categories: ``suggest,'' ``inhibition,'' ``encouragement,'' and ``wish.'' Furthermore, we categorize individual personality traits into five dimensions (the Big Five), and also consider their age and sex.We then analyze how the perception of each type of behavioral facilitation information varies according to these traits. Our analysis reveals that during disasters, the interpretation of behavioral facilitation information exhibits distinct and consistent patterns depending on the personality traits of the victims.